2002
DOI: 10.1021/la020218u
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics of Thin Amorphous Water Films on Surfaces

Abstract: The paper presents experimental investigation of the crystallization kinetics of thin (from several and up to 100 monolayers, ML) amorphous ice films grown in a vacuum on clean and adsorbate modified Pt(111) and graphite (0001) surfaces. The crystallization kinetics was followed by the associated decrease of the desorption rate by isothermal desorption mass spectroscopy. The process is strongly substrate dependent for thin films (below 20-30 ML), gradually becoming substrate independent in 30-100 ML range, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
98
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 40 publications
6
98
1
Order By: Relevance
“…Previous isothermal TPD studies of the adsorption of water on HOPG and on Pt{111} have shown that the time taken for crystallization becomes independent of film thickness for sufficiently thick films. 15 However, this was not observed for the adsorption of water on HOPG as shown in Figure 5B. Note that for low exposures (e6 langmuirs), region A is followed directly by region C. This implies that, for exposures e6 langmuirs, desorption of multilayers takes place simultaneously with the crystallization of the ASW.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Previous isothermal TPD studies of the adsorption of water on HOPG and on Pt{111} have shown that the time taken for crystallization becomes independent of film thickness for sufficiently thick films. 15 However, this was not observed for the adsorption of water on HOPG as shown in Figure 5B. Note that for low exposures (e6 langmuirs), region A is followed directly by region C. This implies that, for exposures e6 langmuirs, desorption of multilayers takes place simultaneously with the crystallization of the ASW.…”
Section: Resultsmentioning
confidence: 86%
“…A temperature of 142 K was chosen in accordance with previous isothermal TPD studies of water on HOPG. 12,14,15 Figure 5A shows an isothermal TPD spectrum recorded following a 40 langmuir exposure of water on HOPG. The spectrum is divided into three regions, labeled A, B, and C. Initially there is an increase in the desorption rate as desorption of the adlayer takes place during both the initial temperature ramp and with the sample held at 142 K. The desorption rate then rapidly decreases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystallization kinetics will provide information about the properties of supercooled liquid water. A variety of experimental techniques (including desorption, [16][17][18][19][20] physisorption, 11,21-24 infrared spectroscopy, 5,10,[25][26][27][28] and electron microcopy 12,29 ) have been used to study ASW crystallization. The majority of the above mentioned studies report that crystallization occurs via bulk nucleation although a few studies suggest that nucleation may start at the vacuum interface.…”
mentioning
confidence: 99%